Combined ultrasound-laccase assisted bleaching of cotton - Basto, Carlos (2007)
This study evaluates the potential of using ultrasound to enhance the bleaching efficiency of laccase enzyme on cotton fabrics. Ultrasound of low intensity (7 W) and relatively short reaction time (30 min) seems to act in a synergistic way with the enzyme in the oxidation/removal of the natural colouring matter of cotton. The increased bleaching effect could be attributed to improved diffusion of the enzyme from the liquid phase to the fibres surface and throughout the textile structure. On the other hand inactivation of the laccase occurred increasing the intensity of the ultrasound. However, at the ultrasound power applied in the bleaching experiments the loss of enzyme activity was not significant enough to justify the use stabilizer such as polyvinyl alcohol. Furthermore, the polyvinyl alcohol appears to be a substrate for the laccase.